Struktur Kekuasaan pada Konflik Sosial dalam Film Badik Titipan Ayah Sutradara Dedi Setiadi (Analisis Wacana Kritis): Power Structure in Social Conflict in the Film Badik Titipan Ayah by Director Dedi Setiadi (Critical Discourse Analysis) - Aimah, Ummu; Agussalim AJ, Andi; Hajrah`, Hajrah (Journal Studies in Indonesian Language and Literature, 2025)
This research is a qualitative descriptive study aiming to reveal the power structure within the social conflicts depicted in the film Badik Titipan Ayah directed by Dedi Setiadi. The approach used is Norman Fairclough’s Critical Discourse Analysis, which views language as a social practice that reflects power relations. Data were obtained through content analysis of the film’s dialogues that illustrate forms of dominance and social control. The results show that power is represented through characters such as Karaeng Tiro, who imposes his will on family members, and through social pressure directed at those who resist social and traditional norms. Language functions as a tool of control, affirmation of social status, and construction of identity. These findings confirm that the social conflicts portrayed in the film are inseparable from the power structures operating through discourse.